Prospective Study On Statins Effect On Clinical Outcomes Among Non-Dialysis Ckd Patients: A Comparison Between A Hospital In Malaysia And Saudi Arabia - Kharshid, Abeer Mohammad Nimer (2019)
Chronic Kidney Disease (CKD) is a global health concern which constitutes a considerable share of the diseases burden around the world. For controlling the progress of CKD, many strategies have been proposed. However, there are still many questions to be answered in this segment of clinical practice especially in countries like the Kingdom of Saudi Arabia (KSA) and Malaysia. The aims of this study are to investigate the renoprotective effect and complications of different doses/types of statins (arm A of the study), to evaluate the health-related quality of life of Malaysian and Saudi ND-CKD patients (arm B), and to assess pharmacists and physicians knowledge and awareness about using statin in CKD patients in the Malaysian and the Saudi hospitals and healthcare settings (arm C).